2020
DOI: 10.26434/chemrxiv.12895754
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent Control over Sequence and Dispersity in Multiblock Copolymers

Abstract: <p>Controlling monomer sequence in synthetic macromolecules is a major challenge in polymer science and the order of building blocks has already been demonstrated to determine macromolecular folding, self-assembly and fundamental polymer properties. Dispersity is another key parameter in material design, with both low and high dispersity polymers displaying complementary properties and functions. However, synthetic approaches that can simultaneously control both sequence and dispersity remain experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…For reversible addition fragmentation chain transfer polymerization (RAFT), temporally controlling the addition of monomeric retarders [ 36 ] or radical species generators [ 37 ] provides opportunities to govern dispersity. Unique to RAFT and its use of chain transfer agents (CTAs), Đ can be regulated by controlled addition of CTAs over time, [ 38 ] mixing of CTAs, [ 6c,d ] or using switchable CTAs [ 39 ] that behave differently depending on the nature of the organic solvents.…”
Section: Synthetic Approaches For Tuning đmentioning
confidence: 99%
“…For reversible addition fragmentation chain transfer polymerization (RAFT), temporally controlling the addition of monomeric retarders [ 36 ] or radical species generators [ 37 ] provides opportunities to govern dispersity. Unique to RAFT and its use of chain transfer agents (CTAs), Đ can be regulated by controlled addition of CTAs over time, [ 38 ] mixing of CTAs, [ 6c,d ] or using switchable CTAs [ 39 ] that behave differently depending on the nature of the organic solvents.…”
Section: Synthetic Approaches For Tuning đmentioning
confidence: 99%
“…[ 12‐15 ] Matyjaszewski and others designed MWD controlling protocols by altering catalyst concentrations [ 16‐18 ] or post‐synthetic blending [ 19 ] based on atom transfer radical polymerization (ATRP). The Anastasaki group disclosed that the combination of different chain transfer agents (CTAs) [ 20 ] and variation of CTA reactivity [ 21 ] are attractive to tailor MWDs for homopolymers and multiblock copolymers based on reversible addition‐fragmentation chain transfer (RAFT) polymerization. Goto and coworkers developed dispersity control based on the gradually changed chain‐end reactivity in an alkyl iodide‐mediated RDRP.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[1][2][3][4] The extensive customisability of multiblock copolymers has led to an ever-growing list of synthesis routes and multiblock compositions. 1,[5][6][7][8][9][10] Reversible deactivation radical polymerization (RDRP) has been shown to be a powerful synthetic route ever since the pioneering work in 2011, 5 which employed Cu(0)-mediated radical polymerization to synthesize high-order multiblock copolymers. Of particular value has been the implementation of reversible addition-fragmentation chain transfer (RAFT) polymerization in synthesis of multiblock copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular value has been the implementation of reversible addition-fragmentation chain transfer (RAFT) polymerization in synthesis of multiblock copolymers. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] RAFT processes are of keen interest due to their good monomer compatibility, robustness to experimental conditions and heterogeneous system viability. [23][24][25][26][27][28] Early works employing RAFT polymerization showed that without any intermediate purification, consecutive polymer blocks with high conversion could be synthesized by careful selection of conditions to maximise chain end fidelity (livingness).…”
Section: Introductionmentioning
confidence: 99%